Early intervention of child abuse: An intra familial-approach - Zaini, Mimi Fitriana; Haidar, Zulfan (2014)
The current study investigates the need of intra-familial intervention on children abuse from the parents’ perspective.The current study exposes some scientific evidences while presenting some observable facts of abusive characters among parents towards their children.The fact that family plays big roles in forming children’s characters is also discussed here.The current research particularly presents the phenomenon of child abuse within family setting as the results of lacking intra-familial relations.This technical and qualitative research paper emphasizes on the paramount importance of the need of early intervention of abuse from the family intervention.The consequences of familial abusive can be early identified and intervened with three ways; 1) intra-familial communication, 2) intra-familial interaction,3) intra-familial attachment. The facts of behavioral consequences of abuse towards children are also included to present the detrimental impacts of lacking intra-familial interventions.The current study also highlights the previous research findings on various issues pertaining to children abuse as reference.A sample of two parents was selected randomly for the purpose of the study.A semi-structured interview was conducted to the parents to gain their insight perception on the importance of intra-familial intervention on children abuse.It was found that; 1) parents perceive intra-familial intervention as crucially important, 2)parents perceive of intra-familial communication and interaction as significant to prevent misunderstanding among family members especially to create a sense of belongingness in each other, 3) parents also perceive intra-familial relation is essentially important to develop children’s attitude and to shape their behavior, 4) parents perceive intra-familial intervention is an important early intervention creating attachment in the family to prevent abusive patterns of behavior from parents as well as among siblings towards young children at home.